Risk factors for age related cataract in a rural population of southern India: the Aravind Comprehensive Eye Study - Nirmalan, P K (Copyright 2004 British Journal of Ophthalmology, 2004)
Aim: To determine risk factors for lens opacities and age related cataract in an older rural population of southern India. Methods: A cross sectional population based study of 5150 people aged 40 years and above from 50 clusters from three districts in southern India. The lens was graded and classified after dilation using LOCS III system at the slit lamp for cataract. Definite cataract was defined as nuclear opalescence ⩾3.0 and/or cortical cataract ⩾3.0 and/or PSC ⩾2.0. Results: Definite cataracts were found in 2449 (47.5%) of 5150 subjects and the prevalence of cataract increased with age. The age adjusted prevalence of cataract was significantly lower in males (p = 0.0002). Demographic risk factors—increasing age and illiteracy—were common for the three subtypes of cataract; females were more likely to have cortical cataracts and nuclear cataracts. Additionally, nuclear cataracts were associated with moderate smoking (OR:1.28, 95% CI:1.01 to 1.64), lean body mass indices (OR: 1.37, 95% CI: 1.17 to 1.59) and higher waist to hip ratios (OR: 0.67, 95% CI: 0.54 to 0.82); cortical cataracts with hypertension (OR: 1.39 95% CI:1.11 to 1.72), pseudoexfoliation (OR:1.53,95% CI:1.17 to 2.01), and moderate to heavy smoking; and posterior subcapsular cataracts with diabetes (OR:1.55, 95% CI:1.12 to 2.15), lean body mass (OR:1.32, 95% CI:1.11 to 1.57), and high waist to hip ratios (OR: 0.77, 95% CI: 0.62 to 0.94). Conclusions: Risk factors for age related cataract in this population do not appear to be different from those reported in other populations. Further studies are required to identify the reason for the high prevalence of age related cataract and to understand better the role of each risk factor for cataractogenesis in this population.